Rational Pile Design using Computer-based Program Coding in Matlab: A Case Study - Hoa, Cao Van (Engineering, Technology & Applied Science Research, 2024)
Scientific approaches to pile design have made significant progress in recent years. However, despite these advancements, estimating the axial resistance and settlement of piles still heavily relies on empirical correlations. The design of resource-efficient and environmentally friendly piles is a pressing need. Yet, there is no explicit theoretical or practical experience to guide pile design rationally. Typically, determining a pile’s resistance and settlement is treated as separate problems without considering the interactions between the pile and the soil. Additionally, soil data are inconsistent due to the heterogeneous and isotropic character of the soil in the half-space under the foundation. In this study, the modified Fellenius Unified method was coded in Matlab and applied to analyze pile behavior, considering the resistance and settlement of each pile, as well as interactions between piles and the soil simultaneously. The results showed that this approach is promising for practical applications. Moreover, its implementation in the evaluation of pile design for an apartment project in Binh Duong, Vietnam, suggests that the pile’s length can be reduced even further than it currently is.